Healing in Nurses After Assignment in Natural Disasters - Solikhah, Fitriana Kurniasari; Aditya, Ronal Surya (Folia Medica Indonesiana, 2022)
Highlight : • Disasters impact a large number of people, including nurses who are deployed in the disaster relief. • Culturally sensitive psychological first aid sessions, post-assignment in crisis situations monitoring, and grit have implications in pushing the nurses to overcome their trauma and obstacles. • Government policies are also important in helping nurses to heal after deployment in disaster relief. Abstract : Disasters are defined as catastrophic occurrences that impact a large number of people quickly and with an abrupt onset. On average, one natural disaster is reported globally each day. However, the impact of a traumatic occurrence on an individual may be compared to a rock colliding with the surface of a water body. Systematic searches were conducted in Cochrane, Google Scholar, PubMed, Scopus, Embase, and Web of Science databases. The following keywords were used to perform a literature search: "nurse," "healing," and "natural catastrophes". As a result of reviewing 362 abstracts and titles, ten were determined to meet the study goals. The research methods in four of the ten literatures were qualitative, five quantitative, and one was a blend of both. Generally, culturally appropriate psychological first aid sessions, post-natural disaster assignment monitoring, and grit push people to overcome obstacles and accomplish achievements over time. Nurses who have been deployed to natural catastrophes must heal and need time to rest physically and mentally. This study aimed to find out the implications of culturally sensitive psychological first aid sessions, post-assignment in crisis situations monitoring, and grit in pushing individuals to overcome obstacles and achieve success over time; and how the government policies relate to trauma recovery.